Applied microbiology - Durieux, Alain; Simon, Jean-Paul (Focus on biotechnology ;, 2001)
This book illustrates the major trends in applied microbiology research with immediate or potential applications. The diversity of the chapters allows coverage of a large field of applications, such as food and health sectors, environmental technology, and fine chemical productions. It includes specific research papers and overview papers, and attempts to provide a balanced coverage of various types of micro-organisms, particularly yeast, fungi, and bacteria. It presents results of recent researches, which have immediate application. Audience: The book is intended for research workers in microbiology, in food fermentation, and also to researchers in metabolic engineering. Furthermore, this book will be of interest to people from the academic world and the biotechnological industry.